Comparison of patients satisfaction with aesthetic outcomes following lower extremity reconstruction: Muscle vs. fasciocutaneous free flaps. Issue 1 (January 2021) - Seyidova, Nargiz; Anderson, Keith; Abood, Ahid
Summary: Background: The microsurgical reconstruction of complex lower limb defects has become a routine procedure with high success rates. The emphasis has changed from ensuring flap 'success' to providing a reconstruction, which is also aesthetically pleasing. The aim of this study was to compare patients' satisfaction with aesthetic outcomes, following muscle or fasciocutaneous free flap reconstruction to the lower limb. Methods: Data were collected retrospectively between July, 2013 and May, 2018 at a single institution. The inclusion criteria were adult patients who had successful free tissue transfers to the lower limb following any aetiology. A Likert Scale questionnaire was sent to all patients who met these criteria. The questionnaire included questions related to the reconstruction and donor site. Results: Questionnaires were sent to 83 patients who met the inclusion criteria. Forty-seven (57%) patients responded, of which 22 (47%) underwent reconstruction with muscular flap and 25 (53%) with fasciocutaneous flap. A statistically significant difference between the two groups was found in relation to flap texture ( p = 0.003). Patients with fasciocutaneous flap reconstruction being more satisfied. No significant difference was observed for contour, similarity to the contralateral side, bulkiness of flap, colour match, scar, or overall appearance. The comparison of donor site results revealed no significant difference between the two groups Conclusions: Despite increase in success in lower extremity reconstruction, many patients still find aesthetic results suboptimal and this affects an individual's global sense of well-being. Aesthetic restoration should be viewed as an integral part of lower limb reconstruction. Level of evidence: Therapeutic, III